(untitled) (American Journal of Chemistry and Pharmacy, 2024)
The incredible properties of formulated and commercial Aloe vera herbal soaps have been thoroughly investigated revealing their potent phytochemical and antibacterial effects. The samples were collected from Rupandehi, Lumbini Province. Aloe vera soap was carefully formulated using a cold process. Through disc diffusion, the soap antibacterial effect was tested against harmful gram-positive and gram-negative bacteria, including Escherichia coli and Staphylococcus aureus. The impressive results showed a maximum zone of inhibition (ZOI) of 8 mm and 7 mm for formulated soap, respectively. This was due to the presence of important bioactive compounds such as tannins, saponins, and reducing sugar, which are abundant in Aloe vera extract. Interestingly, the ZOI was less noticeable at lower concentrations of 100 mg/mL, 50 mg/mL, and 25 mg/mL. The formulated soap still exhibited similar properties to the commercial soap, with a pH of 9.7, moisture content, and foam stability. Additionally, the formulated soap had a mixture content of 4.6%, 0.52% free caustic alkali, and a foam stability test measurement of 6.5 cm. These remarkable results highlight the antibacterial potential of Aloe vera-based soap, proving its effectiveness against harmful microorganisms.